New records of Pristidactylus nigroiugulus Cei, Scolaro & Videla, 2001 (squamata: Leiosauridae) with a geographic distribution map - Avila, Luciano Javier (2016)
We provide new geographic records for Pristidactylus nigroiugulus Cei, Scolaro & Videla, 2001 from Argentina. We present the first record for Santa Cruz province and the southernmost records of the species based on lizards collected in the austral summers of 2012/2013 and 2013/2014. Based on a museum specimen, we extend the species distribution to the eastern part of the Somuncurá Plateau. An updated distributional map is included.